Dose reduction of the female breast in chest CT - Seidenfuß, Anna; Mayr, Andreas; Schmid, Matthias; Uder, Michael; Lell, Michael (American Journal of Roentgenology, 2014)
Organ-based tube current modulation has been shown to significantly reduce the radiation dose to the female breast in phantom studies. We sought to assess the proportions of female breast and glandular tissues that are within the range of organ-based tube current modulation in different age groups and whether these proportions could be optimized by clothing. The secondary objective of our study was to determine whether metal parts of brassieres cause artifacts that impair the diagnostic value.Five hundred seventy-eight female patients undergoing chest CT were included in this study. Two hundred nine patients were prospectively examined wearing a brassiere (group A), and the control patients (group B; n = 369) were scanned according to our previous standard without wearing a brassiere during CT. The two groups were subdivided according to cup size (A-E). For CT data acquisition, an angle-dependent tube current modulation, which reduces the tube current for anterior tube position to minimize direct exposure to anteriorly located organs, was used. The proportion of breast tissue and glandular tissue located within and outside the region of tube current reduction was assessed.The results showed that 60.4% of total breast tissue and 67.1% of glandular tissue was inside the region of tube current reduction in group B; the proportions were significantly improved, to an average of 91.3% and 96%, respectively, in group A. Diagnostically relevant artifacts were introduced in none of the patients. Patients' age correlated with this effect, with higher rates of improvement in the older patient group. Angle-dependent tube current modulation was most effective in patients with cup size A while wearing a brassiere. In this group, 97.5% of breast tissue and 98.1% of glandular tissue was inside the region of tube current reduction. Women with a cup size of E had the largest effect of wearing a brassiere, increasing the rate of breast tissue that was affected by angle-dependent tube current modulation from 30.0% to 83.3% and that of glandular tissue from 31.8% to 90.0%.We show that wearing a brassiere increases the percentage of breast tissue within the region of reduced tube current and, therefore, improves the performance of angle-dependent tube current modulation technique.
EVALuna2:5472